(untitled) (The Journal of Medicine, Humanity and Media, 2025)
Objective: This study examines the association between technological emotions cultivated through digital engagement and digital resilience among youth. This study uses a mediation-moderation model to explore the factors influencing youths’ digital resilience and its underlying mechanisms. Methods: The study collected data using the online survey platform Diaoyanjia, with undergraduate students serving as the primary research subjects. A total of 493 questionnaires were collected, of which 469 were valid, yeilding a response rate of 95.13%. Results: (1) technological emotions had a significant positive relationship with youths’ digital resilience; (2) prosocial behavior mediated the relationship between technological emotions and youths’ digital resilience; (3) this mediation process was moderated by digital literacy. Specifically, the relationship between prosocial behavior and digital resilience is stronger among youth with low digital literacy than for those with high digital literacy. Conclusion: This study offers a new perspective for understanding youths’ digital resilience, emphasizing that in a digital environment filled with both risks and opportunities, youth not only need to develop positive and rational technological emotions, but also require support and empowerment from social systems.